(untitled) (Medico Legal Update, 2019)
Fire, one of the pure elements forming the world and one of the elements to provide life energy to all living beings, sometimes turns deadly. In Forensic Medicine departments, one of the most common cases for post mortem examinations is Burns case. But it becomes difficult many a times to comment on the manner of death in cases with a brief survival period. So, the currentretrospective study was undertaken at Mortuary complex of GMERS Medical college,Dharpur-Patan, Gujarat during the period from 1st Jan 2016 to 31stDec 2017.